THE DEVELOPMENT OF HALAL TOURISM THROUGH INNOVATION IN INDONESIA - Wiryanto, Wisber; Walujo, Djoko; Adnan, Asmadi; Hutapea, Gustaria; Nuryana, Mu’man (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Halal tourism is a leading sector of economic income for development if managed properly through innovation. Therefore, it is considered necessary to conduct research on how the application of halal tourism innovations in Indonesia. This paper addresses a research question: What are the developments in halal tourism through innovation in planning, implementation, and evaluation? This study aims to identify the planning, implementation, and evaluation of such halal tourism innovations in Indonesia after the Fatwa of the Council of Indonesian Ulama Number 108/DSN–MUI/X/2016 concerning Guidelines for the Implementation of Tourism Based on Sharia Principles. The research uses library research involving online methods for collecting secondary data. Qualitative descriptive methods and policy analysis techniques are used to analyze the planning, implementation, and evaluation of the development of halal tourism through innovation in Indonesia. The results show that innovations in halal tourism policies remained minimal. Therefore, the government must foster innovation for the development of halal tourism in Indonesia.